Digital agriculture profile: Guatemala - Kropff, Wietske; Martinez, Karen Michelle; Hernandez, Monica Paola; Navarro Racines, Carlos Eduardo; Bouroncle, Claudia; Giraldo Mendez, Diana Carolina; Martinez Salgado, Jesus David; Rios, David; Eitzinger, Anton; Ramirez Villegas, Julian Armando (2024)
Digital technology is set to transform the agricultural sector in Guatemala. These innovations address important challenges faced by farmers, such as climate-related risks, access to real-time alerts and advice, access to credit and insurance, and post-harvest losses. This profile prioritizes several digital technologies based on their relevance to address specific challenges, taking into account their current levels of technological advancement and digital readiness, as well as their potential impact. The selection process balances gender inclusivity and technologies that specifically benefit smallholders. Successful implementation of these technologies requires a holistic approach, encompassing the creation of an enabling environment for digital technologies to reach their full potential. For this reason, the profile outlines recommendations for the creation of business networks and ecosystems, policy and regulation, finance and investment, capacity building, and user-centered design approaches. Ensuring that digital technologies are designed with factors such as affordability, digital literacy and education in mind is crucial for smallholder farmers, thereby preventing the digital, income, and well-being gaps from widening. This comprehensive approach ensures a future of sustainability and prosperity, where the fusion of tradition and innovation drives the nation’s agricultural success.